RNA Virus Gene Signatures Detected in Patients With Cardiomyopathy After Chemotherapy; A Pilot Study - Varkoly, Kyle; Tan, Shaoyuan; Beladi, Roxana; Fonseca, David; Zanetti, Isabela Rivabem; Kraberger, Simona; Shah, Chintan; Yaron, Jordan R.; Zhang, Liqiang; Juby, Michael; Fath, Ayman; Ambadapadi, Sriram; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Viral infections are pervasive and leading causes of myocarditis. Immune-suppression after chemotherapy increases opportunistic infections, but the incidence of virus-induced myocarditis is unknown. Objective: An unbiased, blinded screening for RNA viruses was performed after chemotherapy with correlation to cardiac function. Methods: High-throughput sequencing of RNA isolated from blood samples was analyzed following chemotherapy for hematological malignancies (N = 28) and compared with left ventricular ejection fraction (LVEF). Results: On initial rigorous analysis, low levels of influenza orthomyxovirus and avian paramyxovirus sequences were detectable, but without significant correlation to LVEF (r = 0.208). A secondary broad data mining analysis for virus sequences, without filtering human sequences, detected significant correlations for paramyxovirus with LVEF after chemotherapy (r = 0.592, P < .0096). Correlations were similar for LVEF pre- and post- chemotherapy for orthomyxovirus (R = 0.483, P < 0.0421). Retrovirus detection also correlated with LVEF post (r = 0.453, p < 0.0591), but not pre-chemotherapy, but is suspect due to potential host contamination. Detectable phage and anellovirus had no correlation. Combined sequence reads (all viruses) demonstrated significant correlation (r = 0.621, P < 0.0078). Reduced LVEF was not associated with chemotherapy (p = NS). Conclusions: This is the first report of RNA virus screening in circulating blood and association with changes in cardiac function among patients post chemotherapy, using unbiased, blinded, high-throughput sequencing. Influenza orthomyxovirus, avian paramyxovirus and retrovirus sequences were detectable in patients with reduced LVEF. Further analysis for RNA virus infections in patients with cardiomyopathy after chemotherapy is warranted.